Entrepreneurial Process: A Case of Deep Jyoti Family Resort and Restaurant Pvt. Ltd (Pravaha, 2018)
This paper carries the empirical as well as conceptual review regarding the entrepreneurial process and attempts to explore the entrepreneurial process in the tourism and hospitality enterprise creation in semi-urban area of Nepal. Pravaha Vol. 24, No. 1, 2018, Page: 50-57